2013
DOI: 10.1016/j.compfluid.2013.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of Volume-of-Fluid and Level-Set methods by relevance to dendritic ice growth in supercooled water

Abstract: a b s t r a c tTwo relevant computatio nal models, one relying on a Level-Set approach, the other one on a Volume-ofFluid tracking procedure with piecewise linear inter face reconstruction, are comparatively assessed in terms of their capability to simulate crystallizatio n of supercooled water. The models are preliminary validated by computing a one-dimensional freezing front propagation for which an analytic solution exists. Afterwards, the tip velocity of two-dimensional dendrites growing in supercooled wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Once nucleated, the ice front can propagate after the exothermal heat has dissipated through the bark (Shibkov et al, 2003), whereby propagation rates within the water column are proportional to the degree of supercooling (Langer et al, 1978;Rauschenberger et al, 2013). In excised branches of P. abies, propagation rates similar to those found in this field study were observed (2 and 4 mm s 21 for 1.5 and 2 K of supercooling, Table I.…”
supporting
confidence: 70%
“…Once nucleated, the ice front can propagate after the exothermal heat has dissipated through the bark (Shibkov et al, 2003), whereby propagation rates within the water column are proportional to the degree of supercooling (Langer et al, 1978;Rauschenberger et al, 2013). In excised branches of P. abies, propagation rates similar to those found in this field study were observed (2 and 4 mm s 21 for 1.5 and 2 K of supercooling, Table I.…”
supporting
confidence: 70%
“…The heat fluxes in the solidq s and the liquidq l are determined through the Fourier heat conduction lawq = −k∇T, where the gradient of the temperature fields is calculated through second-order one-sided finite differences [29]. Because of the iterative algorithm, the heat fluxes are closely linked to the mass source termṁ and the released enthalpy of fusion at the interface.…”
Section: Freezing/meltingmentioning
confidence: 99%
“…Because the phase change does not only change the mass in every cell but also the cell energy, the temperature in all boundary cells needs to be updated after every inner iteration step [29].…”
Section: Freezing/meltingmentioning
confidence: 99%
“…[7,31] has been correspondingly modified towards fulfilment of an appropriate accuracy level with respect to the thermal energy equation discretization and the approximation of the temperature normal derivative close to the interface.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…In the present work, a computational model based on the level set technique [27] used in Refs. [6,7,31] has been appropriately modified, aiming at increasing the accuracy level of the discretization of the equation governing the thermal energy and the normal-to-interface derivative of the temperature field. The model describes the freezing mechanism under supercooled conditions, relying on the physical and mathematical description of the twophase moving-boundary approach (minimal model of solidification) considering kinetic effects.…”
Section: Introductionmentioning
confidence: 99%